Peran Motivasi Belajar Dalam Meningkatkan Prestasi Belajar Siswa Kelas 4 Di Sekolah Dasar Muhammadiyah - Subhan Adi Santoso (Universitas Muhammadiyah Gresik, 2024)
Individuals learn existence (stimulus) from the outside world and possibly patterns from within because there are dynamic principles within each individual. The following are the dynamic aspects of this person: Goal seeking, mind, and drive: Goal seeking is the process by which an individual's behavior is focused on achieving certain goals; mind is a qualitative substance distinct from physical, and drive is the individual's internal driving force, more generally referred to as